Management of sleeve gastrectomy leakage with endoscopic stenting - Dogan, Fadli; Dincer, Mürsit (International Surgery Journal, 2019)
Background: Sleeve gastrectomy is one of the most commonly applied procedures for obesity surgery. Leakage from the stapler line and bleeding are the most important complications of sleeve gastrectomy. This study aimed to report the results of esophageal stent procedure applied to cases who developed leaks after sleeve gastrectomy. Methods: This study included patients who had sleeve gastrectomy due to morbid obesity and were detected to have a leak after the procedure. Demographic features, time of leakage after the surgery, and the management of the leak were analyzed. Results: it was detected in this study, 1220 cases who had sleeve gastrectomy for morbid obesity. Leaks were developed in 10 patients after Laparoscopic Sleeve Gastrectomy (LSG). Four patients, followed conservatively without stent application, were excluded. Six patients, treated with stent application, were included. Two of the patients were males, and four were females (M/F=1/2). The mean age was 38.3 (±11.57) (range: 26-58). The mean body mass index was 43.26 (±2.10)kg/m2. The incidence of a leak was 0.81%. Conclusions: In a conclusion, stents can be safely applied by experienced endoscopists for the management of sleeve gastrectomy leakage.